Competency-based curricula and technology: Game changers for literature subjects in secondary schools in Arusha city, Tanzania - Cheema, Guneet Kaur; Rather, Mohd Aarif; Aggarwal, Vandana; Mandloo, Showket Ahmad; Faustino, Anagrolia (Journal of Interdisciplinary Studies in Education, 2026)
This study examines the impact of competency-based curricula (CBCs) and technology on teaching and learning literature in English among secondary schools in Arusha, Tanzania. Critical thinking, creativity and student participation were not much promoted in the traditional teacher-centered practices of Tanzania’s education system. The introduction of CBC addressed this challenge by promoting a learner-centered approach emphasizing skills and competencies required in the twenty-first century. A mixed-methods approach was adopted in the present study to collect data from both instructors and students at various schools through surveys, interviews and classroom observations. The findings reveal that CBCs increases student engagement and participation in English literature by motivating students to develop critical analytical skills through active learning. Thereafter, technology integration including digital resources, online platforms and multimedia tools, significantly enhances the educational curriculum by providing diverse text material and encouraging an interactive learning atmosphere. The study also emphasizes the need for professional development of instructors and adequate technological infrastructure. Overall, the results of this study reveal that when a competency-based curriculum is integrated with technology, it makes the literature in English education more interesting, dynamic, resourceful and successful, preparing students for the globalized digital world.